Preparation of partially neutralized poly(acrylic acid) microspheres via inverse pickering suspension polymerization - Ceylan, Ozgur; Kaya, Mehmet Arif; Sarac, Ayfer (WILEY, 2019)
Partially neutralized poly(acrylic acid) (PAA) microspheres have been prepared by Inverse Pickering Suspension Polymerization (IPSP) using 1,2-dichlorobenzene (DCB) and hydrophobic fumed silica nanoparticles (HFSi-NPs) as organic dispersing media and dispersing agent respectively. As crosslinker N,N'-methylene bisacrylamide (MBAc), as initiator potassium persulfate (KPS) and sodium metabisulfite (SMBS) redox couple were used. Neutralization degrees were adjusted using 8N NaOH solution and polymerizations were initiated at 34 degrees C. Water/oil phase ratio was set to 1/7 for all polymerizations. Morphology of prepared dry poly(acrylic acid) beads was examined by two microscopic methods, scanning electron microscopy (SEM) and optical microscopy. Prepared microsized polymer beads were observed as smooth and spherical in shape. Effect of neutralization degree (alpha) varied from 70% to 90% on absorptions in both distilled water and saline solutions, absorption under load (AUL) and crosslink density (CD) results were also investigated. POLYM. ENG. SCI., 59:162-169, 2019. (c) 2018 Society of Plastics Engineers
Keywords: Engineering; Polymer Science